Innate immunity dictates cytokine polarization relevant to the development of pulmonary fibrosis - Strieter, Robert M.; Keane, Michael P. (The Journal of Clinical Investigation, 2004)
New data support the importance of the innate immune response in the resolution or progression of pulmonary fibrosis. The presence of CXC chemokine receptor 3–expressing cells, specifically pulmonary NK cells, is necessary to produce IFN-γ. This is critical in the polarization of the immune response to injury toward a favorable Th1 response and resolution. In contrast, a Th2 response is associated with progressive fibrosis.